Direct and Inverse Cinematic Resolution Calculation using Denavit-Hartenberg Algorithm and Geometric Method for Robot with 5 DOF (LACCEI, 2024)
This manuscript aims to shine light on the analysis done for the direct and inverse kinematics of a 5 DOF robot. Where the main objective is to add a 5th degree of freedom to a traditional SCARA robot due to the extent of the study, it was fitting to cover in a more in-depth manner the control system separately to continue to add to the state of the art. It was possible to solve the direct and inverse kinematics of a SCARA robot of 5 DOF using DenavitHartenberg algorithm and geometric method, respectively. The Denavit-Hartenberg algorithm solves kinematics based on homogenous transformation matrices to pass through one system to another using the coordinates systems of every joint and link. Geometric method allows to solve complex kinematics in a simplified way by considering just the coordinates that provides finite solutions. A successful control system for a SCARA of 5 DOF could be built using these two methods.